Urothelial carcinoma: the evolving landscape of immunotherapy for patients with advanced disease - Dietrich B; Srinivas S (Research and Reports in Urology, 2018)
Brian Dietrich,1 Sandy Srinivas2 1Department of Hematology/Oncology, Stanford University School of Medicine/Stanford Cancer Center, Stanford, CA, USA; 2Department of Oncology, Stanford University School of Medicine/Stanford Cancer Center, Stanford, CA, USA Abstract: Urothelial carcinoma is the sixth most common malignancy in the US. While most patients present with non-muscle-invasive disease, many will develop recurrent disease including some progressing to muscle invasive metastatic cancer. Treatment outcomes have remained poor and stagnant for those with more advanced illness, with typical 5-year survival rates in the range of ≤15%. While first-line, platinum-based chemotherapy remains the current standard for those eligible, the recent incorporation of checkpoint inhibitors into the management of advanced bladder cancer has resulted in an expansion of treatment options for a difficult-to-treat disease. This review will discuss the historic standard treatment options, followed by the more recent evolving role immune therapy has in the management of bladder cancer. Keywords: urothelial, immunotherapy, checkpoint inhibitor, bladder cancer